[OP.4B.05] RELATIONSHIPS BETWEEN ALCOHOL INTAKE AND LEFT VENTRICULAR DIASTOLIC FUNCTION IN HYPERTENSION: A TISSUE-DOPPLER STUDY. (September 2016) - Catena, C.; Colussi, G.L.; Novello, M.; Nait, F.; Pezzutto, F.; Sechi, L.A.
Abstract : Objective: Studies on heavy alcoholic drinkers have reported an association between alcohol intake and left ventricular (LV) function. The effect of moderate alcohol intake on LV function in hypertensive patients, however, is unknown. The aim of the study was to investigate the relationship between alcohol consumption and LV function in hypertension. Design and method: In 335 non-alcoholic essential hypertensive patients (age 52 ± 14 years, 177 males, 129 never treated with antihypertensive drugs) we measured anthropometric parameters, fasting plasma glucose, lipids, and liver tests, and 24-h creatinine clearance. Patients with an history of alcohol addiction (DSM IV), previous major cardiovascular events, LV ejection fraction <50%, and 24-h creatinine clearance <30 ml/min 1.72 m 2 were excluded. Average daily alcohol consumption was estimated by a questionnaire (AUDIT) and patients were classified in 4 different levels (level 1 = 0 g/day, n = 172; level 2: 1–19 g/day, n = 85; level 3: 20–39 g/day, n = 55; level 4: more than 40 g/day, n = 23). LV function was assessed by both conventional echocardiography and tissue-Doppler imaging (TDI). Results: LV inner diastolic and systolic diameter, interventricular septum thickness, and LV mass index were progressively greater with increasing levels of alcohol consumption. LV ejection fraction, early/late transmitral flowrate, and isovolumic relaxation time did not differ across patients with different levels of alcohol intake, whereas left atrial diameter increased progressively with increasing alcohol intake. TDI detected LV diastolic dysfunction in 167 (49.8%) of hypertensive patients and e' wave velocity was inversely related with alcohol consumption showing progressively impaired LV diastolic function. Patients with LV diastolic dysfunction were older, more frequently diabetics, and had higher body mass index, systolic and diastolic blood pressure, plasma glucose, cholesterol, triglycerides, GGT, and AST, and LV mass index. Multivariate logistic regression analysis of factors associated with LV diastolic dysfunction indicated that alcohol intake was a significant predictor independent of age, body mass index, blood pressure, diabetes, and LV mass index. Conclusions: In hypertensive patients without a history of alcohol addiction and normal LV systolic function, daily alcohol consumption is independently associated with LV diastolic dysfunction.